Neural activity during processing Chinese irony text: An event-related potential study - Shi, Hanwen; Li, Yutong (Frontiers in Neuroscience, 2022)
Objective Irony as an indirect language with unpredictability consumes more cognitive resources, and is more difficult to understand than literal language. This study aims to explore the processing differences between irony and literal sentences using event-related potential (ERP) technology. Materials and methods Three types of sentences were involved: sentences with predictable literal meaning, sentences with unpredictable literal meaning, and sentences with ironic meaning. The neural responses of the subjects were recorded when they read sentences. Results Compared to predictable literal meaning sentences, unpredictable literal meaning sentences and ironic meaning sentences elicited larger amplitude of N400 components. The difference was not significant between the latter two. In addition, there was no significant difference in P600 evoked by the three sentences. Conclusion In the initial stage of irony processing, the low predictability may result in the difficulty in semantic comprehension, in which the processing patterns of unpredictable and ironic sentences are rather close. In the later stage of processing, ironic integration is not harder compared to literal sentence integration.